2003
DOI: 10.1081/cbi-120025247
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment of Eclosion Rhythm inDrosophila melanogasterPopulations Reared for More Than 700 Generations in Constant Light Environment

Abstract: In this paper, we report the results of our extensive study on eclosion rhythm of four independent populations of Drosophila melanogaster that were reared in constant light (LL) environment of the laboratory for more than 700 generations. The eclosion rhythm of these flies was assayed under LL, constant darkness (DD) and three periodic light-dark (LD) cycles (T20, T24, and T28). The percentage of vials from each population that exhibited circadian rhythm of eclosion in DD and in LL (intensity of approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…For cyanobacteria kept in constant light, strains with a functional clock are outcompeted by strains with a mutant clock, suggesting that the clock is of no benefit or even detrimental in constant conditions (Woelfle et al 2004). By contrast, Drosophila raised for 700 generations in constant light retain entrainable circadian rhythms, which the authors suggest is indicative of the circadian clocks having an intrinsic adaptive value (Paranjpe et al 2003). Of course, animals from arrhythmic habitats are natural examples of these experimental conditions, and provide another method to test the Day Within hypothesis.…”
Section: What Can Be Gained In Our Understanding Of the Evolution Of mentioning
confidence: 99%
“…For cyanobacteria kept in constant light, strains with a functional clock are outcompeted by strains with a mutant clock, suggesting that the clock is of no benefit or even detrimental in constant conditions (Woelfle et al 2004). By contrast, Drosophila raised for 700 generations in constant light retain entrainable circadian rhythms, which the authors suggest is indicative of the circadian clocks having an intrinsic adaptive value (Paranjpe et al 2003). Of course, animals from arrhythmic habitats are natural examples of these experimental conditions, and provide another method to test the Day Within hypothesis.…”
Section: What Can Be Gained In Our Understanding Of the Evolution Of mentioning
confidence: 99%
“…On the contrary, circadian rhythms were found to persist in cave-dwelling fishes [98], in cave-dwelling millipedes [99], and in populations of D. melanogaster that had been reared for more than 600 generations under constant laboratory conditions [100-102]. Furthermore, in one of our recent studies we found that eclosion [103] and locomotor activity (Paranjpe et al, unpublished data) rhythms of these flies entrain to a wide range of periodic LD cycles ranging from 20 h to 28 h. In addition, these flies responded to brief light pulses by shifting the phase of their locomotor activity rhythm in a phase-dependent manner, quite similar to the wild type flies maintained under LD cycles (Paranjpe et al, unpublished data). Thus, it appears that important clock features such as period, precision, phase-relationship; phase response properties and ability to entrain to a wide range of LD cycles remain intact in organisms living in constant environments.…”
Section: Clocks In the Darkmentioning
confidence: 99%
“…However, interspecies comparison among different hours showed no significant difference. There is a persistence of circadian rhythmicity in an aperiodic environment for several generations (Paranjpe et al 2003), as in the present situation. Organisms living in periodic and constant environments confer adaptive value by co-coordinating various cyclic metabolic processes to external environmental cycles (Pittendrigh 1993).…”
mentioning
confidence: 67%